The Use of Translanguaging in Arabic Language Classroom at Higher Education - Sari, Risna Rianti; Muassomah, Muassomah; Bahruddin, Uril; Hasanah, Mamluatul (Arabi : Journal of Arabic Studies, 2024)
Arabic teachers have a negative attitude toward translanguaging in the process of learning Arabic. But in fact, they use other languages than Arabic in their teaching. This condition prompts to reveal translanguaging in Arabic language classes. The aim of this study was to explore the patterns of translanguaging in the process of learning Arabic and to reveal the reasons the teachers used it. Case study methods selected for data collection. The result is that translanguaging has a different pattern in each skill taught through input-process-output. On the fourth input process the skill remains using Arabic, whereas for learning nahwu the input process used Indonesian. The learning process of listening and writing skills remains with Arabic; reading skill, speaking skill and nahwu used Indonesia. They use translanguaging in the learning process to ensure students' understanding of content, build communication and to promote their metalinguistic awareness in the Arabic language learning process.